Transcriptomic analysis of identical twins with different onset ages of adrenoleukodystrophy - Fu, Chuhua; Su, Qiuyu; Chen, Yinglian; Zhang, Yonghui; Zhang, Yan; Cao, Ying; Wang, Xinggang; Zhen, Zhiming; Liu, Chen; Yang, Zhao; Yin, Changlin; Tan, Liang (Frontiers in Neuroscience, 2025)
IntroductionAdrenoleukodystrophy (ALD) is a rare X-linked neurogenetic disease caused by mutations in the ATP-binding cassette subfamily D member 1 (ABCD1) gene. Currently, the molecular mechanisms underlying the onset and severity of ALD remain unclear. Therefore, the aim of this study is to identify information on candidate genes associated with the onset and severity of ALD by transcriptome sequencing of whole blood samples from monozygotic twin families with the disease.MethodsThe identification of differentially expressed genes (DEGs), set theory analysis, gene enrichment analysis, and classification statistics of expression trends have been executed to acquire potential candidate genes inducing the onset and severity of ALD in patients. The study cohort comprised eight individuals: two normal children, two pediatric twins with ALD, the twins’ mother, their adult uncle with ALD, the twins’grandmother, and one normal adult.ResultsFive distinct sets of differentially expressed genes (DEGs) were identified using whole blood samples from a family of identical twins with different onset ages and ABCD1 exon 2 deletions. Then, 39 DEGs of A ∩ B ∩ C − D and A ∩ B − D, as well as 425 DEGs of C ∩ E, were considered as genes relating to the onset and severity of ALD. In particular, C4BPA, TPBG, CEP112, CHST15, SMAD1, IL-26, and LRRC69 have shown more importance than others in ALD onset. Furthermore, KEGG and GO enrichment further suggested the role of Ca2+ homeostasis and the plasma membrane in ALD onset and severity. Finally, expression pattern analysis further demonstrated the pivotal role of the selected DEG sets.DiscussionThe information on candidate genes of this study was considered crucial for preliminarily exploring the molecular mechanisms related to the onset and severity of ALD, which offered novel insights and research directions for mitigating and treating the development of ALD.